从诗歌和仕女图中分析唐寅笔下女性的寓意 = Analysis the meaning of women from Tang Yin’s poetry and painting of the figures of ladies - 陈巧瑾 Chen, Qiao Jin (2017)
在封建社会思想的长期累月地影响下，女子在社会的地位是极其卑微，是附属于男权社会的存在。明代才子唐寅才华横溢，书画冠绝，尤其是在仕女画上的造诣极高。但是他和当时古代的大多数男子不同，对于女性，唐寅除了有着深切的同情，同时也赋予了女性极高的称赞和赏识。故此，本文想从文图学的角度出发，通过分析诗歌中特有的女性意象、仕女图的细节与题画诗，剖析出唐寅对女性的观念及其成因。笔者发现唐寅对于女性的喜爱不仅仅是因为在他的生活中有许多的机会接触各种各样的女性，而发掘出女性性格的积极一面，同时因为女性和他在当时社会的地位是相似的，因此产生一种惺惺相惜的情感。With the continuous influence of feudal society, the social status of women is inferior and is attached to patriarchal society. Ming Dynasty Genius, Tang Yin, is very brilliant and good at painting, especially his high attainments of painting of the figures of ladies. However, Tang Yin is different from the majority of men in ancient times, he got deep compassionate for women, and he also gave a high praise and appreciation to women. Therefore, this article analyses how did Tang Yin think of women and reasons behind from the various aspects of text theories by the analysis of poetry in the unique image of women. I found that not only there were many opportunities for Tang Yin to meet and deal with different kinds of women but he also found out the aspect of initiative personalities of women whom are similar social status as Tang Yi. Perhaps that might be the reason why they really value and appreciate one another.